Preventive and Promotional Effort for Type 2 Diabetes Mellitus based on Local Resources - Oliva Suyen Ningsih; Fransiska Widyawati; Bonavantura N Nggarang; Alberika Sindriyani D Jehoman; Dorotea Nasvia; Karolus Fransiskus Tono (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The people of Gendang Rejeng are potentially at a higher risk of type 2 diabetes due to their unhealthy lifestyle and eating habits linked to their traditional practices. There are efforts to identify the potential risk of type 2 diabetes and carry out preventive and promotive measures based on local potentials. The efforts include: 1) health check-ups; 2) diabetes screening; 3) health education; and 4) discussion with community leaders on adapting traditional practices to be more health-friendly. Through the study we discovered that out of 29 people of Gendang Rejeng that had been screened for diabetes, 62.1% had a low risk, 13.8% had a higher risk, and the remaining 24.1% had a moderate risk of diabetes. There is a need to study local potentials and traditional elements which can be incorporated into the efforts to reduce the risk of diabetes and prevent other health complication. Ginger is an example of one of the local potentials that can be utilized for consumption to improve the health of the people of Rejeng